"Merging Yoga and Occupational Therapy (MY-OT): A feasibility and pilot study". (October 2016) - Schmid, Arlene A.; Puymbroeck, Marieke Van; Portz, Jennifer D.; Atler, Karen E.; Fruhauf, Christine A.
Highlights: Prior work in yoga and occupational therapy are reviewed. The Merging Yoga and Occupational Therapy intervention is proposed as to manage fall risk factors after stroke. Balance, balance confidence, and fall risk factor management improved after the MY-OT intervention. Abstract: Objective: To examine the feasibility and benefits of the Merging Yoga and Occupational Therapy (MY-OT) intervention. Design: This is the primary analysis of a non-controlled pretest-posttest pilot study to understand the feasibility and impact of MY-OT on balance, balance self-efficacy, and fall risk factor management in people with chronic stroke. Setting: University research laboratory. Participants: People with chronic stroke were included in the study if they: had sustained a fall or had fear of falling, were able to stand, and hand impaired balance and were at risk for falls (≤46 on the Berg Balance Scale (BBS)). Interventions: Individuals completed an 8 week intervention that included 16 sessions of both yoga and group occupational therapy (OT). Yoga included physical postures, breathing exercises, and meditation. OT focused on post-stroke fall risk factor management. Main outcome measures: The BBS was used to assess balance, the Activities-specific Balance Confidence Scale (ABC) was used to measure balance self-efficacy. Five fall risk factor management scales were used. Results: Overall, the intervention was considered feasible, as individuals were able to safely complete the intervention with little attrition and high attendance. Balance improved by 30% (p = 0.002). Balance self-efficacy improved by 15% (p = 0.034). Each of the five fall risk factor management scales improved, but only two significantly improved (Fall Prevention and Management Questionnaire, 29%, p = 0.004 and Fall Prevention Strategy Survey, 42%, p = 0.032). Conclusion: The results demonstrate that MY-OT is a potential intervention to improve multiple fall related outcomes for people with stroke. Therapists may consider these interventions for people with stroke, but additional research is warranted.